A Study on Barriers to Adoption of Electric Vehicles - Manjula. B. C; Shilpa. B. S; Sundaresh. M (East Asian Journal of Multidisciplinary Research, 2022)
Adoption of green& sustainable technologies in the transport sector is the need of the hour. High initial price charging time & limited range are the obstacles towards the adoption and diffusion of electronic vehicles. Deployment of electronic vehicle has been a key measurers to reduce pollution in urban areas caused by the logistic sector. A technology emerged more than a century ago EV failed in its several encounters with the gas powered cars and the efforts to penetrate the market. Though much progress has been made in the past decade, the wide adoption of EVs is still in question. In the process of reducing the pollutions world is searching for every alternative to reduce the emissions and find the solutions to the alternative energy’s. The study aims to find out those barriers to the adoption of electric vehicles. The articles is contemporary and examines the different factors that affect a consumer’s adoption of an EV.